The Use of Lipids and Fatty Acids to Measure the Trophic Plasticity of the Coral Stylophora subseriata. Issue 3 (21st December 2012) - Seemann, J.; Sawall, Y.; Auel, H.; Richter, C.
Abstract: Following up on previous investigations on the stress resistance of corals, this study assessed the trophic plasticity of the coral Stylophora subseriata in the Spermonde Archipelago (Indonesia) along an eutrophication gradient. Trophic plasticity was assessed in terms of lipid content and fatty acid composition in the holobiont relative to its plankton (50–300 μm) food as well as the zooxanthellae density, lipid, FA and chlorophyll a content. A cross‐transplantation experiment was carried out for 1.5 months in order to assess the trophic potential of corals. Corals, which live in the eutrophied nearshore area showed higher zooxanthellae and chlorophyll a values and higher amounts of the dinoflagellate biomarker FA 18:4n‐3. Their lipid contents were maintained at similar to levels from specimens further away from the anthropogenic impact source going up to 14.9 ± 0.9 %. A similarity percentage analysis of the groups holobiont, zooxanthellae and plankton >55 μm found that differences between the FA composition of the holobiont and zooxanthellae symbionts were more distinct in the site closer to the shore, thus heterotrophic feeding became more important. Transplanted corals attained very similar zooxanthellae, chlorophyll a and lipid values at all sites as the specimens originating from those sites, which indicates a high potential for trophic plasticity in the case of a change in food sources, which makes this species competitive and resistant to eutrophication.